Reception of Penelope’s Character in 20th Century Poetry: Female Modernism and Latvian Writer Aspazija - Eiduka, Dina (Literatūra, 2023)
Penelope, the wife of Odysseus, has held a prominent position in literature since the time of Homer. Throughout the ages, numerous authors have engaged with Penelope and incorporated her into various contexts, contributing to her enduring recognition in the modern world. She serves as a muse for authors who delve into contemporary issues and address the pertinent challenges of their time. This article explores the development of the reception of Penelope’s character in the beginning of 20th century, tracing its origins from the texts of Homer and Ovid. It specifically examines the utilisation of Penelope in the poetry of modernist poets, particularly those associated with the category of Female Modernism (as proposed by Jane Dowson in her work “Women, Modernism and British Poetry, 1910–1939: Resisting Femininity” (2002)), with a particular focus on the works of the Latvian author Aspazija.
Keywords: reception; Penelope; feminism; Female Modernism; Aspazija